Characterization of operating conditions for ball bearings through design of experiment [electronic resource] - Muhammad Fadlee Abu Bakar, 1988-; Adnan Hassan, supervisor (2012)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2012